The diagnostic pathway and prognosis in bulbar-onset amyotrophic lateral sclerosis. - Turner, M; Scaber, J; Goodfellow, J; Lord, M; Marsden, R; Talbot, K (2010)
BACKGROUND: Despite the inevitability of disease progression in amyotrophic lateral sclerosis, there is a high degree of prognostic heterogeneity in all subtypes. Some bulbar-onset (BO) patients may develop rapid anarthria yet remain ambulant for a prolonged period, whereas others progress rapidly, with early generalisation of motor weakness to the limbs and respiratory muscles. Diagnostic delay is a common occurrence in ALS, and many BO patients report having attended other specialist clinics prior to diagnosis. METHODS: A retrospective descriptive study of BO ALS patients seen in a tertiary clinic over a six year period. RESULTS: Forty-nine BO ALS patients were studied. Median survival from symptom onset was 27 months (range 6-84). 63% of subjects were female and the mean age at symptom onset was 68 years. Half had been referred to another speciality prior to diagnosis, either otolaryngology or stroke clinics, but this did not influence diagnostic latency or survival. Emotionality was reported in 45% of patients. Neurophysiological assessment was performed in 80%, brain imaging recorded in 69%, and antibody testing for myasthenia gravis in 22%. The median time to symptomatic progression beyond the bulbar region was approximately 1 year, with equal proportions progressing to the upper or lower limbs. The median interval from onset to anarthria was 18 months, and to loss of ambulation 22 months. There was a close correlation between the two (r(2)=0.6) and median survival from loss of ambulation was only 3 months. Gastrostomy was carried out in 78% of patients with a median time of 13 months from symptom onset, and 3 months from diagnosis. Median survival from gastrostomy was 10 months. CONCLUSIONS: Survival in bulbar-onset ALS is highly variable. Half of the patients were referred to an inappropriate clinic prior to diagnosis. The time interval to the development of anarthria predicted the timing of subsequent loss of ambulation accurately from which survival may then be only a few months.